2016
DOI: 10.4048/jbc.2016.19.4.447
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Pain after Breast Cancer Treatment: A Questionnaire-Based Study on the Prevalence, Associated Treatment Variables, and Pain Type

Abstract: PurposePersistent pain is a common side effect of breast cancer treatment. The present study aimed to assess the prevalence, associated treatment-related factors, and the type of pain (neuropathic or nociceptive) in patients who had undergone a unilateral mastectomy.MethodsAll women who underwent a unilateral mastectomy at a University Hospital between 2009 and 2013 were eligible for inclusion. Women with breast reconstruction or active cancer were excluded. Participants were mailed a questionnaire evaluating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
38
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 29 publications
(70 reference statements)
10
38
3
Order By: Relevance
“…This study showed that a significant difference was found between patients with and without pain regarding axillary procedure (P value = 0.03) and ALND was more common than SN in patients with pain. A study by Juhl et al [5] was in agreement with this study, and found no association between ALND and persistent pain. Several previous studies have demonstrated that ALND was a risk factor for developing persistent pain after breast cancer surgery [6,14,24,25].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…This study showed that a significant difference was found between patients with and without pain regarding axillary procedure (P value = 0.03) and ALND was more common than SN in patients with pain. A study by Juhl et al [5] was in agreement with this study, and found no association between ALND and persistent pain. Several previous studies have demonstrated that ALND was a risk factor for developing persistent pain after breast cancer surgery [6,14,24,25].…”
Section: Discussionsupporting
confidence: 92%
“…It was reported in one study that 38.3% of females in the study suffered surgical site pain [5]. The prevalence of pain presented in this study is higher than that reported by previous studies, whereas the prevalence rate reported in this study ranged from 24% to 47% [4,6,7,14].…”
Section: Discussioncontrasting
confidence: 70%
See 3 more Smart Citations